(untitled) (Advances in Knowledge Representation, 2021)
The volume of information produced both in medical research and in clinical practice have required, since much time, the application of computational resources. An important source of real data, which is relevant for research, in addition to being essential for the management of health units, is the set of healthcare patient records of a hospital. Natural language processing (PLN) techniques consist of an important alternative to address this dynamic source in which new data is constantly recorded. The present research is conduct in this context, exhibiting an initiative to extract data from patient’s records in a large hospital using PLN techniques. To reach our goals, we present background information about such techniques, in adddition to methodological steps and partial results of the extraction conducted in the field of gynecology.